2016
DOI: 10.1245/s10434-016-5149-8
|View full text |Cite
|
Sign up to set email alerts
|

Family Screening in Familial Papillary Carcinoma: The Early Detection of Thyroid Disease

Abstract: Screening allows for the early detection of papillary carcinoma and benign thyroid disease and for this reason we recommend that it is performed periodically. However, more studies, with larger sample sizes, are needed to determine the benefit of screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
3
8
0
2
Order By: Relevance
“…It was found that the prevalence of thyroid cancer in at-risk individuals from families with two first-degree relatives is the same as for the general population (4.6% vs. 4.5%, respectively) and is significantly lower than the rate of thyroid cancer in kindred with three or more firstdegree relatives affected (22.7%) (20). Another prospective study by Rios et al involving nine families with two members affected and one family with three members affected reported that 5% of screened at-risk individuals had thyroid cancer, similar to the present-study cohort in kindreds with two affected members and to the incidence in the general population (26). These results are in agreement with Charkes' probability estimates that in kindred with two first-degree family members affected, the probability that the disease is sporadic or a chance occurrence is as high as 62%, but that it decreases to <6% when three or more members are affected (27).…”
Section: Discussionsupporting
confidence: 82%
“…It was found that the prevalence of thyroid cancer in at-risk individuals from families with two first-degree relatives is the same as for the general population (4.6% vs. 4.5%, respectively) and is significantly lower than the rate of thyroid cancer in kindred with three or more firstdegree relatives affected (22.7%) (20). Another prospective study by Rios et al involving nine families with two members affected and one family with three members affected reported that 5% of screened at-risk individuals had thyroid cancer, similar to the present-study cohort in kindreds with two affected members and to the incidence in the general population (26). These results are in agreement with Charkes' probability estimates that in kindred with two first-degree family members affected, the probability that the disease is sporadic or a chance occurrence is as high as 62%, but that it decreases to <6% when three or more members are affected (27).…”
Section: Discussionsupporting
confidence: 82%
“…A recent prospective study with yearly screening of atrisk individuals from families with FNMTC at the National Institutes of Health (NIH) by Klubo-Gwiezdzinska et al [48] found thyroid cancer by ultrasound screening in 4.6% individuals from families with two members affected (similar to the estimated prevalence in the general population of 4.5%) [16,49] and in 22.7% of members from families with three or more patients affected. Similar results were reported in a prospective study by Rios et al [50], which screened families with mostly two affected members, and found 5.5% incidence of thyroid cancer. Using a mathematical analysis of the SEER (Surveillance Epidemiology and End Results) database, Charkes [15] concluded that up to 62% of 2-hit families may be sporadic occurrences, while the chance of sporadic DTC in families of three or more affected members is less than 6%.…”
Section: Screeningsupporting
confidence: 90%
“…Un recente studio prospettico con screening annuale di individui provenienti da famiglie con FNMTC ha riportato una prevalenza di cancro della tiroide mediante screening ecografico del 4,6% negli individui provenienti da famiglie con due membri affetti (simile alla prevalenza stimata nella popolazione generale di 4,5%) e del 22,7% degli individui provenienti da famiglie con tre o più pazienti affetti [19]. Analoghi risultati sono stati riportati in uno studio prospettico [20] che ha valutato prevalentemente famiglie con solo due membri affetti, riportando il 5,5% di prevalenza di cancro alla tiroide nei familiari di soggetti con FNMTC.…”
Section: La Questione Dello Screeningunclassified